2015
DOI: 10.1016/j.ctrc.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Experience with targeted next generation sequencing for the care of lung cancer: Insights into promises and limitations of genomic oncology in day-to-day practice

Abstract: Introduction Tumor genotyping using single gene assays (SGAs) is standard practice in advanced non-small-cell lung cancer (NSCLC). We evaluated how the introduction of next generation sequencing (NGS) into day-to-day clinical practice altered therapeutic decision-making. Methods Clinicopathologic data, tumor genotype, and clinical decisions were retrospectively compiled over 6 months following introduction of NGS assay use at our institution in 82 patient-tumor samples (7 by primary NGS, 22 by sequential SGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 25 publications
1
22
1
Order By: Relevance
“…These observations support the idea to expand the NGS testing beyond adenocarcinoma and to include other histologic subtypes such as SCC and even LCNEC, particularly for patients with unusual clinical characteristics such as rapid course of progression, younger age, and no history of tobacco smoking. This is in contrast to the study by Ranganchari et al 23 that showed only 1 driver mutation in SCC (FGFR1), information that did not change the clinical treatment decision. Therefore, the authors concluded that NGS testing in SCC is less likely to alter current practice.…”
Section: Discussioncontrasting
confidence: 99%
“…These observations support the idea to expand the NGS testing beyond adenocarcinoma and to include other histologic subtypes such as SCC and even LCNEC, particularly for patients with unusual clinical characteristics such as rapid course of progression, younger age, and no history of tobacco smoking. This is in contrast to the study by Ranganchari et al 23 that showed only 1 driver mutation in SCC (FGFR1), information that did not change the clinical treatment decision. Therefore, the authors concluded that NGS testing in SCC is less likely to alter current practice.…”
Section: Discussioncontrasting
confidence: 99%
“…Patient-tumor pairs followed at Beth Israel Deaconess Medical Center (BIDMC) with a diagnosis of lung adenocarcinoma were identified through an ongoing Institutional Review Board-approved study [12]. Pathologic data, tumor genotype, toxicity to afatinib and radiographic parameters were gathered from retrospective chart extraction.…”
Section: Methodsmentioning
confidence: 99%
“…Patient-tumor pairs followed at the Thoracic Oncology multidisciplinary clinic at Beth Israel Deaconess Medical Center (BIDMC) with a diagnosis of NSCLC were registered through an ongoing Institutional Review Board-approved study [1719]. Pathologic data, tumor genotype and radiographic images were assembled from retrospective chart extraction.…”
Section: Methodsmentioning
confidence: 99%
“…RNA was isolated from tumor tissue for evaluation of fusion partners using PCR-based or next generation sequencing assays, while DNA was isolated to sequence exons corresponding to the kinase domain of ALK (exons 21 to 27), as previously reported [16, 17, 20, 21]. …”
Section: Methodsmentioning
confidence: 99%